Nitrogen-doped carbon dot material with high emulsification level and preparation method thereof

The synthesis of nitrogen-doped carbon dot materials by solvothermal method solves the problems of long preparation processes and high cost in the prior art, and achieves rapid and economical acquisition of nitrogen-dot carbon dot materials with high emulsion levels to meet the emulsification needs under different oil phase conditions.

CN119797336AActive Publication Date: 2025-04-11JILIN UNIVERSITY

Patent Information

Application Number
CN202510074621.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-11
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

The existing carbon dot material preparation methods have problems such as long preparation procedures, high cost and strict requirements for oxidation reaction conditions, and it is difficult to quickly and economically obtain nitrogen dot carbon dot materials with excellent emulsification effects.

Method used

A nitrogen-doped carbon dot material was synthesized by solvothermal as a carbon source, and nitrogen-doped carbon dot material with high emulsification level was prepared by controlling the reaction time, adjusting the acid amount, and changing the nitrogen source. This method does not require reactor heating, which is cheap and reduces energy consumption.

Benefits of technology

It has achieved the rapid synthesis of a large number of nano-scale nitrogen-doped carbon dot materials with amphiphilic emulsification effect under mild reaction conditions. The obtained nitrogen-doped carbon dot materials are uniform in size and have high dispersion, which can meet the emulsification needs under different oil phase conditions, and are extremely cheap in cost and simple in process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797336A_ABST
    Figure CN119797336A_ABST
Patent Text Reader

Abstract

The invention discloses a nitrogen-doped carbon dot material with a high emulsification level and a preparation method thereof, and belongs to the technical field of two-dimensional interface materials. The method comprises the following steps: firstly, adding a NaOH aqueous solution into an acetaldehyde aqueous solution, then adding hydrochloric acid to adjust the pH value of the solution to be neutral, stirring for reaction, then centrifuging to retain precipitate, extracting with liquid nitrogen, and freeze-drying to obtain a carbon dot material; and adding the carbon dot material into a system of potassium methoxide and a nitrogen source, carrying out heating reaction, carrying out centrifugation, retaining the precipitate, drying, and preparing the nitrogen-doped carbon dot material with a high emulsification level by controlling the reaction time, regulating the acid amount and changing the nitrogen source. A large amount of nanoscale nitrogen-doped carbon dot material emulsifiers with an amphiphilic emulsification effect can be rapidly synthesized under mild reaction conditions, the obtained nitrogen-doped carbon dot material is uniform in size and high in dispersity, the emulsification requirements under different oil phase conditions can be met, the preparation process is simple, dialysis and centrifugation are not needed in industrial production, and the method is suitable for industrial production. And the nitrogen-doped carbon dot material with a high emulsification level can be prepared only through centrifugation and drying.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of two-dimensional interface materials, and in particular relates to a nitrogen-doped carbon dot material with a high emulsification level and a preparation method thereof. Background Art

[0002] Emulsification systems are widely used in food, cosmetics, pharmaceuticals and materials science, but existing emulsifiers often have problems such as toxicity, poor stability and environmental impact. Carbon dot materials are becoming a research hotspot in the field of emulsification due to their unique surface chemical properties and good environmental friendliness. The surface of carbon dot materials is rich in various functional groups (such as hydroxyl, carboxyl and epoxy groups), and their hydrophilicity or hydrophobicity can be regulated by chemical modification. This surface property enables carbon dot materials to form a stable emulsified film at the oil-water interface, thereby improving the emulsification effect. In addition, by adjusting the size, morphology and concentration of carbon dot materials, precise control of emulsification properties can be achieved.

[0003] Compared with traditional emulsifiers, carbon dot materials are non-toxic and biodegradable, which is in line with the current trend of green chemistry and sustainable development. In the field of food and cosmetics, carbon dot materials can replace chemical synthetic emulsifiers to prepare safer and more environmentally friendly emulsified products. In addition, carbon dot materials can significantly improve the long-term stability of the emulsification system. The physical or chemical network structure formed in the emulsion can prevent the emulsion from stratification, aggregation or precipitation.

[0004] In addition, carbon dot materials are usually prepared from cheap and abundant carbon sources, such as glucose, citric acid, waste biomass, etc. In practical applications, the preparation cost of carbon dot materials is relatively low, which is mainly reflected in the following aspects:

[0005] Low price of raw materials: carbon dot materials often use green raw materials (such as peels, vegetable waste, etc.) or industrial by-products, and the cost is much lower than synthetic surfactants; simple preparation process: low-energy preparation processes such as hydrothermal method and microwave method are easy to mass produce, further reducing the manufacturing cost; environmental friendliness: the degradability and non-toxicity of carbon dot materials reduce the cost of waste treatment, which meets the needs of sustainable development. Therefore, it is very urgent to obtain carbon dot materials with excellent emulsification effect.

[0006] The use of post-modification methods to control the amphiphilic properties of carbon dot materials objectively prolongs the preparation process and increases production costs, which is contrary to the current ecological concept of economic and environmental protection. Therefore, it is very urgent to precisely control various oxidation reaction conditions during the preparation of carbon dot materials, shorten the preparation process of amphiphilic carbon dot materials, reduce production costs, and thus obtain carbon dot materials with different amphiphilic properties.

[0007] The currently reported methods for preparing carbon dot materials mainly include "top-down" and "bottom-up". The "top-down" method is to decompose large-sized carbon materials into nano-scale carbon dot materials through laser etching, chemical oxidation and other methods. The "bottom-up" method is to generate carbon dot materials from small molecule organic precursors through hydrothermal method, solvothermal method, pyrolysis method and other methods. Among them, the "bottom-up" method has a higher purity for preparing carbon dot materials. The present invention adopts the solvothermal method. Compared with the hydrothermal method, it does not require the heating of the reactor, the cost is lower and the energy consumption is reduced. Summary of the invention

[0008] The object of the present invention is to provide a nitrogen-doped carbon dot material with a high emulsification level and a preparation method thereof.

[0009] The present invention adopts acetaldehyde as a carbon source to synthesize nitrogen-doped carbon dot materials, and applies the prepared nitrogen-doped carbon dot materials to the emulsification of toluene organic solvent to obtain an emulsion system with a high emulsification level. The nitrogen-doped carbon dot materials with a high emulsification level are prepared by controlling the reaction time, regulating the acid amount, and changing the nitrogen source.

[0010] The method for preparing a nitrogen-doped carbon dot material with a high emulsification level according to the present invention comprises the following steps:

[0011] (1) Prepare 1-3 M NaOH aqueous solution, stir for 15-30 minutes and then let stand;

[0012] (2) slowly adding the NaOH aqueous solution prepared in step (1) dropwise into the 30-50% by mass acetaldehyde aqueous solution, completing the addition within 15-30 minutes and stirring evenly;

[0013] (3) Stirring the system obtained in step (2) for 2 to 5 h at room temperature to obtain a brown-red paste solution;

[0014] (4) Add the hydrochloric acid solution dropwise to the system obtained in step (3), adjust the pH of the solution to neutral, and continue stirring for 4 to 12 hours until the system becomes a golden yellow solution;

[0015] (5) Centrifuging the system obtained in step (4) at 10,000 to 12,000 rpm for 3 to 5 minutes, removing the supernatant after centrifugation and retaining the precipitate;

[0016] (6) Add deionized water to the precipitate obtained in step (5), disperse it evenly by ultrasonication, remove the supernatant after centrifugation, and retain the precipitate; repeat the operation of "adding deionized water to the precipitate - ultrasonication - centrifugation - retaining the precipitate" 2 to 5 times to obtain a brown-red precipitate;

[0017] (7) freeze-drying the brown-red precipitate obtained in step (6) using liquid nitrogen to obtain an orange-yellow carbon dot material;

[0018] (8) Disperse 1-2 g potassium methoxide in 10-20 mL methanol, add 0.5-2 g nitrogen source, and stir until no solid precipitate remains;

[0019] (9) adding the carbon dot material obtained in step (7) to the system in step (8) and heating at 70-90°C for 30-60 minutes;

[0020] (10) The system obtained in step (9) is centrifuged at a speed of 10000-12000 rpm for 3 minutes, the supernatant is removed, and the precipitate is retained and dried to obtain a nitrogen-doped carbon dot material with a high emulsification level.

[0021] Furthermore, in step (2), the volume ratio of the NaOH aqueous solution to the acetaldehyde aqueous solution is 1:1-3, the concentration of the hydrochloric acid solution in step (4) is 1-3 M, the freeze-drying conditions in step (7) are a temperature of -70 to -60°C and a vacuum degree of <10Pa, the nitrogen source in step (8) is urea, lysine, cysteine, glycine, aniline, citrulline, pyridine or arginine, and step (10) is vacuum dried at 70-90°C for 20-30 hours.

[0022] The nitrogen-doped carbon dot material obtained in step (11) is added to deionized water for ultrasonic dispersion to obtain a nitrogen-doped carbon dot material dispersion, and the obtained nitrogen-doped carbon dot material dispersion is then mixed with toluene in a certain volume ratio and shaken, and after shaking, it is quickly transferred to a colorimetric tube, and the emulsification rate is measured after standing for 24 hours to detect its amphiphilic emulsification performance;

[0023] Cottonseed oil and turpentine were used to prepare an oil phase with a gradient HLB value (HLB=7~13). The nitrogen-doped carbon dot material dispersion was then mixed with the gradient HLB value oil phase. The emulsion was prepared by ultrasonic mixing and emulsification at a certain power. The emulsification rate was measured after standing for 24 hours to detect the effect of the gradient HLB value oil phase on the emulsification properties of the nitrogen-doped carbon dot material.

[0024] Table: Data of "gradient HLB value oil phase" prepared by cottonseed oil and turpentine HLB value 7 8 9 10 11 12 13 Cottonseed oil / g 0.845 0.751 0.657 0.563 0.469 0.375 0.282 Turpentine / g 0.15 0.244 0.338 0.432 0.526 0.62 0.713

[0025] The technical solution of the present invention can quickly synthesize a large amount of nano-scale nitrogen-doped carbon dot material emulsifiers with amphiphilic emulsification effect under mild reaction conditions. The obtained nitrogen-doped carbon dot materials are uniform in size and high in dispersion, and can meet the emulsification requirements under different oil phase conditions. The cost is extremely low and the production process is simple. Dialysis and centrifugation are not required in industrial production, and only centrifugal drying is required for preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 : Optical photograph of the nitrogen-doped carbon dot material obtained in Example 1;

[0027] Figure 2 : Transmission electron microscope photo of the nitrogen-doped carbon dot material obtained in Example 1;

[0028] Figure 3 : XRD pattern of the nitrogen-doped carbon dot material obtained in Example 1;

[0029] Figure 4 : XPS image of the nitrogen-doped carbon dot material obtained in Example 1;

[0030] Figure 5 : Infrared image of the nitrogen-doped carbon dot material obtained in Example 1;

[0031] Figure 6 ; Optical photograph of the emulsification effect of the nitrogen-doped carbon dot material obtained in Example 1;

[0032] Figure 7 : Leica electron microscope emulsified bubble image of the nitrogen-doped carbon dot material obtained in Example 1;

[0033] Figure 8 : Surface tension change curve of water / toluene system after adding nitrogen-doped carbon dot material dispersion in Example 1;

[0034] Fig. 9 : Optical photograph of the oil phase with gradient HLB value after adding the nitrogen-doped carbon dot material dispersion in Example 1. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical scheme, effect and advantage of the embodiments of the present invention clearer, the embodiments will be described in more detail and completely below. It should be noted that the embodiments described below are not all embodiments, but only embodiments of the preferred invention conditions of the present invention. The reagents and instruments used in the embodiments can be purchased through normal commercial channels. Based on the embodiments of the present invention, those of ordinary skill in the art directly obtain the present embodiments without creative activities, which belongs to the scope of protection of the present invention.

[0036] Example 1

[0037] (1) Prepare 10 mL of 1 M NaOH aqueous solution, stir for 20 minutes and then let stand;

[0038] (2) Slowly add the NaOH aqueous solution prepared in step (1) dropwise into 20 mL of 40% acetaldehyde aqueous solution, complete the addition within 20 minutes and stir evenly;

[0039] (3) Stirring the system obtained in step (2) for 3 h at room temperature to obtain a brown-red paste solution;

[0040] (4) preparing 30 mL of 1 M hydrochloric acid solution; adding the obtained hydrochloric acid solution dropwise to the system obtained in step (3), adjusting the solution to pH = 7.0, and obtaining a golden yellow solution;

[0041] (5) Centrifuging the system obtained in step (4) at 12,000 rpm for 3 minutes, removing the supernatant and retaining the precipitate;

[0042] (6) Add deionized water to the precipitate obtained in step (5), disperse it evenly by ultrasonication, remove the supernatant after centrifugation, and retain the precipitate; repeat the operation of "adding deionized water to the precipitate - ultrasonication - centrifugation - retaining the precipitate" three times to obtain a brown-red precipitate;

[0043] (7) The brown-red precipitate obtained in step (6) was freeze-dried using liquid nitrogen extraction (-65°C, vacuum degree <10Pa) to obtain 2.2 g of orange-yellow carbon dot material;

[0044] (8) Disperse 1 g of potassium methoxide in 10 mL of methanol, add 1 g of urea, and stir for 10 minutes until no solid precipitates;

[0045] (9) Add 0.25 g of the carbon dot material obtained in step (7) to the system obtained in step (8), and stir at 80° C. for 30 minutes;

[0046] (10) The system obtained in step (9) was centrifuged at 12000 rpm for 3 minutes, the supernatant was removed, and the precipitate was retained and vacuum dried at 80°C for 24 hours to obtain 0.27 g of nitrogen-doped carbon dot material.

[0047] Take 20 mg of nitrogen-doped carbon dot material and add it to 5 mL of deionized water, and ultrasonicate for 10 minutes (frequency 40 Khz) to obtain a nitrogen-doped carbon dot material dispersion. Add the obtained nitrogen-doped carbon dot material dispersion to 5 mL of toluene to form a water-oil system, and then place it on a constant temperature shaker at 300 rpm for 1 hour, transfer it to a glass bottle, seal it and let it stand for more than 24 hours, and measure the height of the emulsion layer H 乳 and the total height H of the oil-water system 总 , according to the emulsification rate = (H 乳 / H 总 )*100%, the emulsification rate is 80%; the average diameter of the emulsified bubbles formed by Leica electron microscope is 38μm. The obtained nitrogen-doped carbon dot material dispersion is added to 5mL of oil phase with gradient HLB value (HLB=7~13), mixed and ultrasonicated for 30 minutes (frequency 40Khz), and left to stand for 24 hours. The HLB value corresponding to the system with the highest stability and emulsified layer height is 10~11.

[0048] Figure 1 It is a nitrogen-doped carbon dot material with a solid material appearance of yellow powder. Figure 2From the transmission electron microscope photograph, it can be seen that the obtained nitrogen-doped carbon dot material has an average particle size of 2~4nm. Figure 3 This is the X-ray diffraction (XRD) spectrum of the nitrogen-doped carbon dot material. It can be seen that the nitrogen-doped carbon dot material has a broad peak at 20 degrees, corresponding to the highly graphitized structure of the nitrogen-doped carbon dot material. Figure 4 This is the X-ray photoelectron spectroscopy (XPS) spectrum of nitrogen-doped carbon dot materials. The peak at 284.8 eV corresponds to graphitized sp2 carbon, and the peaks at 286.1 e V and 287.0 e V correspond to CO and C=O. It can be seen that the surface of nitrogen-doped carbon dot materials has epoxy functional groups such as hydroxyl and carboxyl. Figure 5 This is the infrared (IR) spectrum of nitrogen-doped carbon dots. It can be seen that at 3345cm -1 and 3453cm -1 There is a stretching vibration peak of NH at 1620cm -1 There is a bending vibration peak of NH at , which proves that the amino functional group has been successfully introduced. Figure 6 This is the emulsification effect diagram of nitrogen-doped carbon dot materials. In the water / toluene system, the formed emulsion layer occupies the entire oil phase and part of the water phase (the oil phase is on the top and the water phase is on the bottom), forming a stable Pickering emulsion. Figure 7 The Leica electron microscope emulsified bubble image after adding nitrogen-doped carbon dot material to the water / toluene system shows that the emulsified bubbles formed are uniform in size, with a diameter of 30~50μm. Figure 8 This is the surface tension test change chart. It can be clearly seen that after adding nitrogen-doped carbon dot materials, the surface tension of the water / toluene system dropped from 43.6mN / m to 7.3mN / m, and the interfacial tension of the system was reduced by 83.3%. Fig. 9 This is an optical photograph of the dispersion in Example 1 in the oil phase with a gradient HLB value. It can be clearly seen that the emulsion layers of numbers 10 and 11 have the highest heights and the best stabilization effects, indicating that the HLB value range of the nitrogen-doped carbon dot material is 10-11.

[0049] Example 2

[0050] Steps (1) to (7) are the same as in Example 1, and 2.2 g of orange-yellow carbon dot material is obtained;

[0051] (8) Disperse 1 g of potassium methoxide in 10 mL of methanol, add 0.5 g of lysine, and stir for 10 minutes until no solid precipitates;

[0052] (9) Add 0.5 g of the carbon dot material obtained in step (7) to the system obtained in step (8), and stir at 80° C. for 30 minutes;

[0053] (10) The system obtained in step (9) was centrifuged at 12000 rpm for 3 minutes, the supernatant was removed, and the precipitate was retained and vacuum dried at 80°C for 24 hours to obtain 0.55 g of nitrogen-doped carbon dot material with a diameter of 4~10 nm, an emulsification rate of 55%, and an average diameter of the emulsified bubbles of 45 μm.

[0054] Example 3

[0055] Steps (1) to (7) are the same as in Example 1, and 2.2 g of orange-yellow carbon dot material is obtained;

[0056] (8) Disperse 1 g of potassium methoxide in 10 mL of methanol, add 0.5 g of cysteine, and stir for 10 minutes until no solid precipitates;

[0057] (9) Add 0.5 g of the carbon dot material obtained in step (7) to the system obtained in step (8), and stir at 80° C. for 30 minutes;

[0058] (10) The system obtained in step (9) was centrifuged at 12000 rpm for 3 minutes, the supernatant was removed, and the precipitate was retained and vacuum dried at 80°C for 24 hours to obtain 0.54 g of nitrogen-doped carbon dot material with a diameter of 4~8 nm, an emulsification rate of 56%, and an average diameter of the emulsified bubbles of 48 μm.

[0059] Example 4

[0060] Steps (1) to (7) are the same as in Example 1, and 2.2 g of orange-yellow carbon dot material is obtained;

[0061] (8) Disperse 1 g of potassium methoxide in 10 mL of methanol, add 0.5 g of glycine, and stir for 10 minutes until no solid precipitates;

[0062] (9) Add 0.5 g of the carbon dot material obtained in step (7) to the system obtained in step (8), and stir at 80° C. for 30 minutes;

[0063] (10) The system obtained in step (9) was centrifuged at 12000 rpm for 3 minutes, the supernatant was removed, and the precipitate was retained and vacuum dried at 80°C for 24 hours to obtain 0.55 g of nitrogen-doped carbon dot material with a diameter of 4~10 nm, an emulsification rate of 53%, and an average diameter of the emulsified bubbles of 50 μm.

[0064] Example 5

[0065] Steps (1) to (7) are the same as in Example 1, and 2.2 g of orange-yellow carbon dot material is obtained;

[0066] (8) Disperse 1 g of potassium methoxide in 10 mL of methanol, add 0.5 g of citrulline, and stir for 10 minutes until no solid precipitates;

[0067] (9) Add 0.5 g of the carbon dot material obtained in step (7) to the system obtained in step (8), and stir at 80° C. for 30 minutes;

[0068] (10) The system obtained in step (9) was centrifuged at 12000 rpm for 3 minutes, the supernatant was removed, and the precipitate was retained and vacuum dried at 80°C for 24 hours to obtain 0.58 g of nitrogen-doped carbon dot material with a diameter of 6~9 nm, an emulsification rate of 52%, and an average diameter of the emulsified bubbles of 60 μm.

[0069] Example 6

[0070] Take 20 mL of 40% acetaldehyde aqueous solution and 20 mL of ammonia water (concentration is 27%) and mix them. React at 20°C for 3 hours. Add 30 mL of 1M hydrochloric acid solution and adjust the pH to neutral. The rest of the operation is the same as in Example 1. No carbon dot material is produced after step (7).

[0071] Example 7

[0072] Steps (1) to (7) are the same as in Example 1, and 2.2 g of orange-yellow carbon dot material is obtained;

[0073] (8) Disperse 1 g of potassium methoxide in 10 mL of methanol, add 0.5 g of aniline, and stir for 10 minutes until no solid precipitates;

[0074] (9) Add 0.5 g of the carbon dot material obtained in step (7) to the system obtained in step (8), and stir at 80° C. for 30 minutes;

[0075] (10) The system obtained in step (9) was centrifuged at 12000 rpm for 3 minutes, the supernatant was removed, and the precipitate was retained and vacuum dried at 80°C for 24 hours to obtain 0.57 g of nitrogen-doped carbon dot material with a diameter of 8~10 nm. The emulsification effect was very poor, the emulsion layer was unstable, and the emulsion broke quickly.

[0076] Example 8

[0077] Steps (1) to (7) are the same as in Example 1, and 2.2 g of orange-yellow carbon dot material is obtained;

[0078] (8) Disperse 1 g of potassium methoxide in 10 mL of methanol, add 0.5 g of pyridine, and stir for 10 minutes until no solid precipitates;

[0079] (9) Add 0.5 g of the carbon dot material obtained in step (7) to the system obtained in step (8), and stir at 80° C. for 30 minutes;

[0080] (10) The system obtained in step (9) was centrifuged at 12000 rpm for 3 minutes, the supernatant was removed, and the precipitate was retained and vacuum dried at 80°C for 24 hours to obtain 0.51 g of nitrogen-doped carbon dot material with a diameter of 10-15 nm, an emulsification rate of 51%, and an average diameter of the emulsified bubbles of 70 μm.

[0081] Example 9

[0082] Steps (1) to (7) are the same as in Example 1, and 2.2 g of orange-yellow carbon dot material is obtained;

[0083] (8) Disperse 1 g of potassium methoxide in 10 mL of methanol, add 0.5 g of arginine, and stir for 10 minutes until no solid precipitates;

[0084] (9) Add 0.5 g of the carbon dot material obtained in step (7) to the system obtained in step (8), and stir at 80° C. for 30 minutes;

[0085] (10) The system obtained in step (9) was centrifuged at 12000 rpm for 3 minutes, the supernatant was removed, and the precipitate was retained and vacuum dried at 80°C for 24 hours to obtain 0.53 g of nitrogen-doped carbon dot material with a diameter of 8~10 nm, an emulsification rate of 51%, and an average diameter of the emulsified bubbles of 72 μm.

Claims

1. A method for preparing a nitrogen-doped carbon dot material with a high emulsification level, the steps of which are as follows: (1) Prepare 1-3 M NaOH aqueous solution, stir for 15-30 minutes and then let stand; (2) slowly adding the NaOH aqueous solution prepared in step (1) dropwise into the 30-50% by mass acetaldehyde aqueous solution, completing the addition within 15-30 minutes and stirring evenly; (3) Stirring the system obtained in step (2) for 2 to 5 h at room temperature to obtain a brown-red paste solution; (4) Add the hydrochloric acid solution dropwise to the system obtained in step (3), adjust the pH of the solution to neutral, and continue stirring for 4 to 12 hours until the system becomes a golden yellow solution; (5) Centrifuging the system obtained in step (4) at 10,000 to 12,000 rpm for 3 to 5 minutes, removing the supernatant after centrifugation and retaining the precipitate; (6) Add deionized water to the precipitate obtained in step (5), disperse it evenly by ultrasonication, remove the supernatant after centrifugation, and retain the precipitate; repeat the operation of "adding deionized water to the precipitate - ultrasonication - centrifugation - retaining the precipitate" 2 to 5 times to obtain a brown-red precipitate; (7) freeze-drying the brown-red precipitate obtained in step (6) using liquid nitrogen to obtain an orange-yellow carbon dot material; (8) Disperse 1-2 g potassium methoxide in 10-20 mL methanol, add 0.5-2 g nitrogen source, and stir until no solid precipitate remains; (9) adding the carbon dot material obtained in step (7) to the system in step (8) and heating at 70-90°C for 30-60 minutes; (10) The system obtained in step (9) is centrifuged at a speed of 10000-12000 rpm for 3 minutes, the supernatant is removed, and the precipitate is retained and dried to obtain a nitrogen-doped carbon dot material with a high emulsification level.

2. The method for preparing a nitrogen-doped carbon dot material with a high emulsification level according to claim 1, characterized in that: In step (2), the volume ratio of the NaOH aqueous solution to the acetaldehyde aqueous solution is 1:1-3.

3. The method for preparing a nitrogen-doped carbon dot material with a high emulsification level according to claim 1, characterized in that: The concentration of the hydrochloric acid solution in step (4) is 1~3 M.

4. The method for preparing a nitrogen-doped carbon dot material with a high emulsification level according to claim 1, characterized in that: The freeze-drying conditions in step (7) are a temperature of -70 to -60°C and a vacuum degree of <10Pa.

5. The method for preparing a nitrogen-doped carbon dot material with a high emulsification level according to claim 1, characterized in that: In step (8), the nitrogen source is urea, lysine, cysteine, glycine, citrulline, aniline, pyridine or arginine.

6. The method for preparing a nitrogen-doped carbon dot material with a high emulsification level according to claim 1, characterized in that: In step (10), vacuum drying is performed at 70-90° C. for 20-30 hours.

7. A nitrogen-doped carbon dot material with a high emulsification level, characterized in that: The method is prepared by any one of claims 1 to 6.

Citation Information

Patent Citations

  • Water-soluble carbon quantum dot sustained-release microcapsule and preparation method and application thereof

    CN108160013A

  • Carbon quantum dot nano-emulsion and application of same as disinfectant

    CN109845767A

  • Construction method and application of Pickering micro-emulsion catalytic system

    CN115501875A

  • Carbon quantum dot-containing composition and method for producing same

    US20220380217A1

  • Carbon quantum dots and uses thereof

    US20220401586A1

Cited By

  • Aldehyde-ketone synthetic carbon dots with high emulsification level and excellent wettability and preparation method of aldehyde-ketone synthetic carbon dots

    CN120229707A

  • Aldehyde-ketone synthesized carbon dots with high emulsification level and excellent wettability and preparation method thereof

    CN120229707B